Immunological evaluation of virulence factor Alphα-actinin among women with Trichomonas Vaginalis - Al-hisnawy, Sarah; Al-Jorany, Raad (Jordan Medical Journal, 2025)
Background: Trichomonas Vaginalis infection is one of the most common sexually transmitted infections in women, and α-actinin is one of the most important virulence factors for this parasite. Objective: To evaluate the concentration of alphα-actinin protein in women infected with Trichomonas Vaginalis infection and control groups using ELISA technology. Methods: Two hundred and sixty four of the participating women were included in our current study, who were attending Al-Manathra Hospital, Al-Najaf Hospital, Al-Furat Hospital, and a few outpatient clinics between January and June of 2023. One hundred and thirty two women were included as a control group and one hundred and thirty two were included as patients (they were suffering from vaginal infection Trichomonas Vaginalis). All participants in the study underwent direct culture in diamond culture media by vaginal swab to confirm the presence of the parasite. And also a blood sample was taken for immunological evaluation by ELISA technique. Results: The results showed that the level of α-actinin concentration was higher in the serum of patients infected with the parasite T.vaginalis (509.113 ± 26.401 pg/ml) and this increase was statistically significant (P-value <0.0001) compared to its concentration in the control serum (67.939 ± 8.179 pg/ml). The highest mean rank for α-actinin (78.94 pg/ml) appeared in the (35-44 year) age group, which numbered 35. While the results showed that the lowest mean rank for α-actinin (55.77 pg/ml) appeared in the (25-34 year) age group, which numbered 30. The level of α-actinin concentration, based on the diagnosis of the clinical condition of patients infected with the parasite, had reached its highest level in the group of patients infected and diagnosed suffering from endometriosis (mean rank 77.68Pg/ml). The lowest increase in the level of α-actinin was in the group of patients diagnosed with polycystic ovary syndrome (PCOS, mean rank 55.67 pg/ml). Based on clinical symptoms, the results showed that the highest mean rank for the level of the virulence factor α-actinin appeared in the group of women suffering from a foul odour, where it reached 82.53 pg/ml. The lowest mean rank for α-actinin (67.31pg/ml) appeared in the group of women who suffered from irregular bleeding. Conclusions: The virulence factor α-actinin was significantly and highly secreted in patients infected with the parasite Trichomonas Vaginalis, α-actinin secretion appears to be affected by the woman's age, as the secretion of the virulence factor increases during the period when hormonal balance becomes unattainable in women aged 35-40 years. α-actinin secretion appeared to increase in women diagnosed with endometriosis, which indicated that vaginal bleeding was an appropriate environment for increased secretion of the virulence factor.